Iron transport in Streptomyces pilosus mediated by ferrichrome siderophores, rhodotorulic acid, and enantio-rhodotorulic acid. - Müller, G (1984)
Streptomyces pilosus is one of several microbes which produce ferrioxamine siderophores. In the accompanying paper (G. Müller and K. Raymond, J. Bacteriol. 160:304-312), the mechanism of iron uptake mediated by the endogenous ferrioxamines B, D1, D2, and E was examined. Here we report iron transport behavior in S. pilosus as mediated by the exogenous siderophores ferrichrome, ferrichrysin, rhodotorulic acid (RA), and synthetic enantio-RA. In each case iron acquisition depended on metabolic energy and had uptake rates comparable to that of [55Fe]ferrioxamine B. However, the synthetic ferric enantio-RA (which has the same preferred chirality at the metal center as ferrichrome) was twice as effective in supplying iron as was the natural ferric RA complex, suggesting that stereospecific recognition at the metal center is involved in the transport process. Iron uptake mediated by ferrichrome and ferric enantio-RA was strongly inhibited by kinetically inert chromic complexes of desferrioxamine B. These inhibition experiments indicate that iron from these exogenous siderophores is transported by the same uptake system as ferrioxamine B. Since the ligands have no structural similarity to ferrioxamine B except for the presence of three hydoxamate groups, we conclude that only the hydroxamate iron center and its direct surroundings are important for recognition and uptake. This hypothesis is supported by the fact that ferrichrome A and ferrirubin, which are both substituted at the hydroxamate carbonyl groups, were not (or were poorly) effective in supplying iron to S. pilosus.